Personal Exposure to Fine-particle Black Carbon Air Pollution Among Schoolchildren Living in Ulaanbaatar, Mongolia - Dashnyam, Ulzii; Warburton, Nicole; Brugha, Rossa; Tserenkh, Ichinkhorloo; Davaasambuu, Enkhmaa; Enkhtur, Shonkhuuz; Munkhuu, Bayalog; Lodoysamba, Sereeter; Dashdendev, Baigalmaa; Grigg, Jonathan; et al. (Central Asian Journal of Medical Sciences, 2015)
Objectives: To measure personal exposure to air pollution in children, in Ulaanbaatar, Mongolia. Methods: Since coal burning for domestic heating causes severe air pollution in Ulaanbaatar, we measured personal PM2.5 exposure for children aged 5-12 years during the winter 2013-2014. Results: Peak levels of black carbon PM2.5 exposure >200 µg/m3 between November and March varied significantly with time of day, with the highest peak 18:00-02:00, a nadir 02:00-07:00, followed by a second peak 07:00 -12:00, with another afternoon nadir 12:00-18:00. Children living in Ger districts in a Ger or wooden house, had the highest levels of PM2.5, >500 µg/m3 , with duration of personal peak exposure in Gers 8-fold longer than in wooden houses. Conclusion: Peak exposures in Gers were related to going outside, fire lighting and cooking, whereas in wooden houses peak exposures were related to going outside or opening the door. The least exposure for children was in an apartment or school with the windows shut. Significant levels of personal exposure also occurred during the commute to school, outside playtime, shopping trips and car rides. Opening the window of steam heated apartments for “fresh air cooling” as well as indoor smoking also produced important levels of personal exposure.